IáR analysis of genetic diversity and relationships among sweet potato (Ipomoea batatas) landraces in China - He, X.=700 1 Liu, Q.; Ishiki, K.; Zhai, H.
(En, Fr, Es)
ilus., 33 ref.
Keywords: IPOMOEA BATATAS; VARIACION GENETICA; EVALUACION; ITALIA; ANALISIS IáR